(untitled) (Fiep Bulletin - online, 2011)
This research aimed to identify the effects of a short program of sports massage in the subjective perception of muscle pain and fatigue in general, after the afternoon training of competitive swimmers, male, mean age of sixteen years, five months and 17, duly registered in the Federation Paraibana Aquatics randomly selected from among the members of the team’s main swimming Esporte Clube Cabo Branco, João Pessoa, state of Paraíba.Caracterizado as a case study, the qualitative nature of longitudinal.Foram type chosen two (n = 2) healthy athletes, who met the criteria for minimum of six years of competitive training, being male, being aged out of 15 and 18, having frequency of at least six sessions training per week and participate in other rehabilitation programs after training within the club, to receive ten (10) sessions of sports massage after training, with a minimum of one and maximum of three times per week during the month of May 2006 with the aim of knowing the effects that implementation of a program of massage can bring to the organismo.Para data collection was necessary for the athletes answer an initial assessment, a follow-up interview in each session, answered before and after each application, and an evaluation final.The data analysis was performed by qualitative observation of the subjective responses of records of assessments applicable norms results for both cases were positive and satisfactory relationship with the Muscular Pain and Fatigue for Generalized, Contrasting results were, however satisfactory in case 1 and case 2 insignificante.Podemos to conclude that for the relief of muscle aches and general tiredness, sports massage, in this study, to be viable, but their results are much more dependent on the type of protocol being used, the level of subjective perception of the subjects undergoing the techniques of handling and manipulation of massage techniques used, their type, how long and in what time it is performed, thereby needing More scientific studies that aim and better specify its findings.